Dasylirion micropterum (Asparagaceae), a new species from Sierra Madre Oriental, Mexico - Villarreal-Quintanilla, José A.; Estrada-Castillón, Eduardo; Reyes-Valdés, M. Humberto; Encina-Domínguez, Juan A.; Martínez, Octavio; Hernández-Godinez, Fernando (Phytotaxa, 2016)
Dasylirion micropterum is described as a new species from high elevations of the Sierra Madre Oriental in the Mexican state of Coahuila. It differs from known species of Dasylirion for having ascending dark green leaves, narrow inflorescences, small fruits with narrow wings and its distribution restricted to the western side of the Sierra Madre Oriental. The identity of the new species was confirmed through the sequence of matK and rbcL plastid DNA regions. GenBank sequences accessions are included. An illustration, photos and a distribution map are presented for the new species.